Optimización de la potencia instalada del proyecto hidroeléctrica caluma bajo - Mosquera Bravo, Karla (2009)
In recent years the country has evolved in the electricity sector due to industrial growth which has resulted in increased demand for electricity and because our electricity sector is not in the ability to successfully meet this demand, we have seen in the need for new power sources. To help address this problem we discuss the optimization of the hydroelectric project "Caluma Bajo" which is located in the “Guayas” river basin and sub-basin “Babahoyo” River system. The "Caluma Bajo" has a number of studies since the early INECEL Accomplish various hydrological and meteorological analysis led to the draft "Caluma Bajo" to a Prefactibilidad status, followed by the topic of past graduation and with the help of computer tools is left the project in the state that it is currently Factibilidad. Based on these studies and following the same methodology of work performed under INECEL and topical task forces of the past, the project "Caluma Bajo" is at a more advanced stage of development that is "Installed power optimization of the Central”.